2020
DOI: 10.3928/23258160-20200326-03
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcomes Following Intravitreal Bevacizumab With Laser Versus Laser Photocoagulation Alone for Retinopathy of Prematurity

Abstract: BACKGROUND AND OBJECTIVE: To assess neurodevelopmental outcomes of infants with treatment-warranted retinopathy of prematurity (TW-ROP) treated with intravitreal bevacizumab (IVB) plus diode laser photocoagulation (DLP) compared to DLP alone. PATIENTS AND METHODS: A retrospective review was performed of infants who underwent treatment for TW-ROP with IVB+DLP or DLP alone from 2010 to 2017. Baseline characteristics and coexisting medical comorbidities we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…Although VEGF has been shown to play a key role in neurodevelopment, 7 previous studies have largely found no detriment to neurodevelopmental outcomes in infants treated with IVB. [14][15][16][17][18][19][20] Bayley III scores have been the most commonly used metric to quantify neurodevelopment, and our analysis corroborates the majority of previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Although VEGF has been shown to play a key role in neurodevelopment, 7 previous studies have largely found no detriment to neurodevelopmental outcomes in infants treated with IVB. [14][15][16][17][18][19][20] Bayley III scores have been the most commonly used metric to quantify neurodevelopment, and our analysis corroborates the majority of previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…There have also been studies, mostly with IVB, demonstrating increased risk of neurodevelopmental delays in infants receiving anti-VEGF therapies [ 40 ], but ascribing the neurodevelopment delay to anti-VEGF therapy alone is challenging as the highest risk infants are also those most likely to be treated with anti-VEGF therapies. For example, another study comparing average Bayley-III scores for cognition, language, motor, and neurodevelopmental outcomes found no difference between infants who received off-label IVB with delayed laser therapy compared to those who received primary laser therapy [ 41 ]. Further prospective studies are needed to definitively assess the neurodevelopment risk of anti-VEGF therapy.…”
Section: Treatment: Anti-vascular Endothelial Growth Factor (Anti-vegf) Therapy For Type 1 Ropmentioning
confidence: 99%
“…Des inquiétudes se sont faites jour à la suite de la publication d'études épidémiologiques montrant une association entre traitement par anticorps anti-VEGF et anomalies neuro-développementales à long terme [45]. Ces données restent toutefois à confirmer [46]. La place des anticorps anti-VEGF dans le traitement de la ROP reste donc imparfaitement définie.…”
Section: Synthèse Revuesunclassified